Usufruct rights certification and tenure security: the case of communal forest lands in Meket district of Northern Ethiopia - Sintayehu, M.; Kassa, H. (2010)
Considerable effort is being made for first-time registration of individual farm plot holdings as part of the execution of federal and regional proclamations issued on rural land administration and use in Ethiopia. But common property resources are not consistently included into the process, making the land administration system rather incomplete. This paper attempted to examine the role of usufruct certification on perceived security of tenure of common property resource users, and to identify determinants of tenure security on common property resources. This study was based on field observation and a formal survey in Meket district of Amhara Region in northern Ethiopia. The study employed descriptive statistics and logistic regression model to examine determinants (socio-economic, policy and institutional variables) of perceived tenure security of common property resource users. Results of the analysis revealed that perceived security of tenure over common property resources is influenced by interplay of a number of explanatory variables, with usufruct certification having an outstanding and positive influence.